PEMBERDAYAAN EKONOMI KREATIF BERBAHAN DASAR ROTAN DAN TEMPURUNG KELAPA - Lis Yulitasari; Tulus Suryanto; Syamsul Hilal (Jurnal Abdimas Bina Bangsa, 2023)
This community service activity focuses on "Empowering a Creative Economy Made from Rattan and Coconut Shell as an Effort to Support the Family Economy" in rural areas. This program aims to improve the economic welfare of families by utilizing local resources. Program steps include skills training, product planning, raw material procurement, production, marketing and business management. The program results include creative products such as baskets made from rattan and vegetable ladles made from coconut shells. The impacts include increasing family income, product diversification, community empowerment, use of local raw materials, increasing social welfare, and market development. Overall, this program proves that creative economic empowerment initiatives can be an effective solution for improving the economy of rural families while supporting environmental preservation and social welfare. These findings have positive implications for developing similar programs in other rural areas